Conocimientos y uso del sodio en la alimentación de los adultos de Medellín (Colombia) (2017)
ABSTRACT: Excessive sodium consumption is linked to chronic degenerative diseases. Increased population knowledge about sodium should help reduce it’s consumption. Objective: To compare the knowledge and practices of the use of salt/sodium in food for men and women in Medellin, Colombia. Materials and Methods: Descriptive cross-sectional exploratory study of 155 men and 167 women aged 18-50 from Medellin, Colombia. Participants were given a survey on sodium consumption practices and knowledge. Results: Significant differences were found (p<0.05) by sex, in favor of women, regarding knowledge of arterial hypertension (54.5% vs. men 43.2%), use of salt substitutes (53.9% vs. men 35.5%) and health risk of excess sodium intake (54.5% vs. men 43.2%). 79.4% of women and 84.4% of men enjoy eating foods with salt. Inconsistencies were found in the relationship between knowledge and dietary practices. The factor analysis revealed differences by sex in consumption of fruit with salt, beer drunk from a salt-rimmed glass, and salt substitutes (p=0.0004). Conclusions: There are differences by sex about the knowledge of sodium and its effects on health. There is inconsistency between knowledge about sodium and dietary practices. Keywords: Hypertension, risk factor, cardiovascular disease, salt, sodium.